Systematic Review of Spatial Thinking in Mathematics Education - Riyan Hidayat; Saad, Mohd Rashid Mohd; Ismail, Normala; Noor, Mohd Asri Mohd (Faculty of Teacher Training and Education, Mulawarman University, 2023)
The objective of this study is to perform a comprehensive analysis of existing research on spatial thinking abilities using a Systematic Literature Review (SLR). To achieve this, five search engines (Scopus, SpringerLink, ScienceDirect, ProQuest, and ERIC) were utilized during various stages, including identification, screening, eligibility, inclusion, and data analysis. Adhering to the PRISMA reporting rules, a total of 22 articles were included, selected mainly from the sorted studies. The results of our research indicate that there were four studies conducted using a mixed method approach, while nine studies utilized a quantitative approach, and another nine focused on qualitative methods. The number of studies investigating spatial thinking has consistently increased over the years. The findings section revealed that the majority of studies on this subject were authored by researchers from the USA, followed by authors from Australia, Turkey, Israel, Germany, Spain, China, Slovakia, Japan, Mexico, South Africa, and the United Kingdom.